Self-Selection of Emigrants: Theory and Evidence on Stochastic Dominance in Observable and Unobservable Characteristics - Panu Poutvaara; George Borjas; Ilpo Kauppinen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper uses Danish full population register data from 1995 to 2001 to analyze self-selection of migrants from Denmark. We find that Danish emigrants are more educated and have higher pre-emigration earnings than non-migrants. The earnings of emigrants are not higher only on average, but the earnings distribution for emigrants stochastically dominates that of non-migrants. Furthermore, we also find positive self-selection in terms of residuals from earnings regressions. These results are consistent with the positive selection hypothesis for migrants from a rich and equal country derived from the Roy model. We also derive the stochastic dominance result from the model.
Keywords: F22; J61; J24; 330